What Happened to US Business Dynamism? - Akcigit, Ufuk; Ates, Sina T. (Journal of Political Economy, 2023)
We attempt to understand potential common forces behind rising market concentration and a slowdown in business dynamism in the US economy, through a micro-founded general equilibrium model of endogenous firm dynamics. The model captures the strategic behavior between competing firms, its effect on their innovation decisions, and the resulting “best-versus-the-rest” dynamics. We consider multiple potential mechanisms that can drive the observed changes and use the calibrated model to assess their relative importance, with particular attention to the implied transitional dynamics. Our results highlight the dominant role of a decline in the intensity of knowledge diffusion from frontier firms to laggard ones. We present new evidence that corroborates a declining knowledge diffusion in the economy.